SENSITIVITY OF SUNFLOWER TO WATER DEFICIT THROU GROWTH STAGES AND ROLE OF BALANCED FERTILIZERS ON PRODUCTIVITY - M. M. A. Abdul-Razak,; S. A. Mahmood, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was conducted during spring season of 2014 at the experimental station of field crops department, College of Agriculture, University of Baghdad, Abu Ghraib to study the sensitivity of sunflower growth stages to water stress, fertilizers balance and interaction between them, and their effect on growth, yield, yield components and quality characteristics of sunflower Flamy cultivar. A randomized complete plot design (RCBD) was used with split-plot arrangement by three replicates. Fertilizers levels (F) ]F1: recommended (180 kg N ha-1, 110 kg P2O5 ha-1 and 100kg K2O ka-1), F2:  (NPK), F3: 2NPK, F4: N2PK, F5: NP2K and F6: 2(NPK)[ were represent the main plots while stress treatment (S) represent the sub plots ]S1 50% water depletion (control) S2 80% water depletion at vegetative growth stage, S3: 80% water depletion at flowering and at seed filling stage[. Results showed that the existence of a significant effects of water stress treatment levels on most of the investigated traits, unstressed plants had the superiority over stressed once, by having more fertility, higher head diameter, higher number of seeds per head which all, resulted in improving sunflower seed yield (4.59 ton ha-1). There is no significantly different under stress plants in vegetative growth stage (S2) in both head diameter and seed yield, while the plant at S2 showed higher values in weight 1000 seeds and harvest index. Plants at S4 showed higher water use efficiency. Fertilizers combinations have a significant effect on most of the traits under investigation. Plants under F4 treatment have higher means of fertility percentage, head diameter and head seed number which caused an improvement in seed yield (4.422 ton ha-1), while F5 showed higher 1000 seeds weight. The interaction between two factors was significantly difference in most of the studied traits.